The Influence of Online Customer Review and Celebrity Endorsement on Purchasing Decision of Skintific Products in Shopee: The Role of Brand Image as a Mediating Variable : Case Study of Padang State University Students - Hitiyatul Julia; Fitria Ridhaningsih (International Journal of Economics and Management Research, 2025)
Skintific is a skincare brand that has experienced significant growth through the Shopee platform with a marketing strategy based on customer reviews and celebrity endorsements. This study aims to analyze the influence of Online Customer Reviews and Celebrity Influencers on Purchasing Decisions for Skin-tific products on Shopee, and to evaluate the role of Brand Image as a mediating variable in students at Padang State University. The method used is a quantitative approach through a questionnaire survey to respondents. The results of the study indicate that Online Customer Reviews have a positive and signif-icant effect on Brand Image and Purchasing Decisions, and are a dominant factor in influencing pur-chasing decisions. Celebrity Influencers have a positive and significant effect on Brand Image, but do not have a direct effect on Purchasing Decisions. Brand Image itself has a positive but insignificant ef-fect on Purchasing Decisions, and does not act as a significant mediator between Celebrity Influencers and Online Customer Reviews on Purchasing Decisions. These findings confirm that in increasing pur-chasing decisions for Skintific products on Shopee, customer reviews have a much stronger role than celebrity-based promotional strategies. Marketing strategies that focus on strengthening trust through customer experience are the main key in driving purchasing decisions